Symposium 1: Re-Conceptualising the Boundaries of Networked Learning: The shifting relationship between learners and teachers - Beaty, Liz; Howard, James (Proceedings of the International Conference on Networked Learning, 2010)
Networked learning has the potential to change the perceptions and practice of those engaged in learning within both networked and traditional environments. At the heart of such change is the nature of the relationship between learners and teachers as their roles and responsibilities are transformed. Recognising this, the E-Quality in e-Learning Manifesto (2002) proposed key aspirations for this relationship, identifying a model based on collaboration and co-construction of knowledge. This model was seen to be supported by the concept of the learning community and to have implications for the professional development of H.E. practitioners. We argue that the ideas contained within the Manifesto can be advanced to fully capture the shifting roles and relationships inherent within networked learning. To this end, this paper focuses on a core set of boundary definitions, central to the way networked learning is conceptualised and experienced. Firstly, we revisit the concept of expertise within learning. While we agree that the expert-acolyte dichotomy is no longer pursuant within networked learning, we argue for a new understanding of the role of expertise defined by transient boundaries. Expertise becomes a quality that moves between members of learning networks, dependent upon time, activity and focus. This raises questions for the traditional boundaries drawn between teachers and learners. If we begin to view teachers as fellow learners in a communal process, we must consider how such learning communities are to be defined. A partial answer lies in the dialogue and communication that connects network members, yet this potentially ignores the relevance of content within networked learning. As such, the boundaries between content and communication are considered and found to be less defined that previously presented. The communication that distinguishes networked learning communities forms the basis of the content members both utilise and collaboratively create. Finally, the implications of these boundary discussions for the professional development of H.E. practitioners are addressed. We note the significant challenges faced in preparing practitioners for their changing role, especially in relation to how they re-conceptualise their place in the learning process and the professional values they associate with it. Finally, we argue for the use of networked communities of professional practice as the means to support the development of diverse H.E. practitioners.